Bibliotecas em transformação: estudo de usuários do Sistema de Bibliotecas da UFSM - Filipetto, Adriane Terezinha (2019)
Through this research work, linked to the Post-graduate in Professional and Technological Education at the Industrial Technical College of Santa Maria, we sought to analyze the lacs of the users of the University libraries at the Federal University of Santa Maria in relation to the services and spaces offered by them to the students, professors and technical-administrative staff. To achieve this goal the methodology we adopted is a case study. The data collection was done through an online questionnaire, sent to the students, professors and administrative technicians of the University. After analyzing the data, the results showed that the users do not know the majority of the spaces and services offered by the libraries, which can indicate both the underutilization of many of them and the convenience of a communication plan for dissemination and better orientation of users.